USE OF BIOLOGICAL DMARDS IN PATIENTS WITH PRIMARY VASCULITIS; RESULTS FROM TURKBIO REGISTRY - Yazici, A.; Cefle, A.; Dalkilic, E.; Pehlivan, Y.; Can, G.; Goker, B.; Onen, F. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS